1993
DOI: 10.1111/j.1744-7348.1993.tb04022.x
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced infectivity of Metarhizium flavoviride in oil formulations to desert locusts at low humidities

Abstract: SummaryFormulation in non‐evaporative diluents such as oils is required to exploit the advantages of controlled droplet application methods for biopesticides based on conidial suspensions of entomopathogenic fungi. In laboratory assays on desert locusts (Schistocerca gregaria), formulations of Metarhizium flauoviride conidia in cotton seed oil showed superior performance to water‐based suspensions and this was especially pronounced at low humidities (35% r.h.). The LD50s for oil and water suspensions at 5 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
2
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(133 citation statements)
references
References 7 publications
7
110
2
8
Order By: Relevance
“…As formulações de fungos entomopatogênicos à base de óleo são superiores àquelas à base de água, especialmente em locais onde a umidade é baixa (BATEMAN et al, 1993). Formulações em óleo prolongam a sobrevivência do conídio e diminuem a sensibilidade a radiações UV quando comparada com suspensões aquosas (INGLIS et al, 1995).…”
Section: Persistênciaunclassified
“…As formulações de fungos entomopatogênicos à base de óleo são superiores àquelas à base de água, especialmente em locais onde a umidade é baixa (BATEMAN et al, 1993). Formulações em óleo prolongam a sobrevivência do conídio e diminuem a sensibilidade a radiações UV quando comparada com suspensões aquosas (INGLIS et al, 1995).…”
Section: Persistênciaunclassified
“…This could be due to the fact that M. anisopliae was the least effective and this contained lesser density conidia. Thus, the infection was slow as the speed of kill is related to the number of conidia received by the individual pest (Bateman et al, 1993). Studies by Boopathi et al (2013) also observed that M. anisopliae caused the lowest pathogenic to A. dispersus under laboratory conditions.…”
Section: Resultsmentioning
confidence: 96%
“…This effect was previously reported by Bahiense et al (2006) using M. anisopliae and deltamethrin applied against Boophilus microplus where 36.5% mortality was seen with concentrations ranging between 0.39 and 6.25 ppm of deltamethrin applied alone; mortalities of 16.5%, 55%, and 96.9% with the concentrations of 2.2 Â 10 5 , 2.2 Â 10 6 , 2.2 Â 10 7 up to 2.2 Â 10 8 conidia/ml of the fungus applied alone, respectively; and with mixed treatments causing 68%, 54%, 100%, and 100% using the highest concentration of deltamethrin with the fungal concentrations, respectively. It was expected that concentrations of D-limonene mixed with the fungal concentrations would improve the suspension of the conidia, producing an oily emulsion and increasing the spore density that facilitated the adhesion of the conidia to the larval cuticle and thereby causing higher mortality (Bateman et al 1993). Oily plant extracts have an acaricide effect against ticks (Abdel-Shafy and Soliman 2004); the oily plant extracts of plants belonging to the families Meliaceae, Lamiaceae, Labiatidae, and others, have acaricidal effects against ticks due to their chemical composition.…”
Section: Discussionmentioning
confidence: 99%